A mixed method evaluation of an intervention for parents with mental illness. (October 2019) - Maybery, Darryl; Goodyear, Melinda; Reupert, Andrea; Sheen, Jade; Cann, Warren; O'Hanlon, Brendan; Cuff, Rose
Let's Talk About Children is a manualised intervention for parents with a mental illness that aims to impact positively on family dynamics. Previous evaluations focused on parents with an affective disorder. The purpose of this study was to evaluate the intervention for parents with various mental illnesses and explore parents' self-reported views regarding the impact of the intervention. A quasi-experimental approach was employed to compare outcomes for parents who received Let's Talk About Children plus treatment as usual ( n  = 20) with a wait list control (treatment as usual) group ( n  = 19), using family functioning and parenting stress questionnaires. Questionnaires were completed 2 weeks prior to receiving the intervention and 4 to 6 weeks after the final session. The wait list parents completed the same questionnaires at two time periods, 6 weeks apart. Semi-structured interviews were conducted after the intervention. Both intervention and control groups showed improvements in parenting and family functioning. Interview data highlighted (1) increased insight, (2) normalising of the illness in the family, (3) family communication changes, (4) the importance of supporting the parenting role and (5) suggestions for additional supports. There are possible issues regarding the influence of psycho-education when giving participants information about the nature of the research.